Improved fatigue life of floating offshore wind turbine towers with tuned mass damper inerters (TMDIs) - Fitzgerald, Breiffni; Broderick, Brian (My University, 2023)
Floating offshore wind turbines (FOWTs) are the largest rotating structures on earth. FOWTs are very flexible and dynamically sensitive, they are also installed in very harsh environments and exposed to stochastic environmental loading from wind and ocean waves. In recent years dampers have been installed in the towers of offshore wind turbines to mitigate vibrations. In this paper, structural dynamic models are used to demonstrate improvements in the fatigue life of FOWT towers when they are equipped with a new type of damper - the tuned mass damper inerter (TMDI). A multi-body dynamic approach is used to model the wind turbine and the TMDI installed in the tower. The model is subjected to stochastically generated wind and wave loads of varying magnitudes to develop wind-induced probabilistic demand models for towers of FOWTs under model and load uncertainties. Numerical simulations are carried out to determine the improvements in fatigue life of FOWT towers that can be achieved by installing TMDIs in comparison to traditional tuned mass dampers (TMDs). The results show that the TMDI outperforms the classical TMD when considering fatigue life.
XII International Conference on Structural Dynamics
PUBLISHED
Delft
Keywords: Smart & Sustainable Planet; Renewable energies; Structural Engineering; Wind Energy and Wind Turbines; Wind, Wind Energy Engineering